THE SHAKING DISASTER OF OCTOBER 2005 – AFTERMATH AND EXPERIENCES: The Shaking Disaster of October 2005 - PAFMJ, Editorial Committee (Pakistan Armed Forces Medical Journal, 2006)
On 8th October 2005 an earthquake struck Kashmir and Northern part of Pakistan. The intensity of earthquake was 7.6 on Richter’s Scale. Initially the magnitude of disaster was not evident, but soon it was realized that this was a major earthquake which caused widespread destruction. The worst hit areas were Azad Jammu & Kashmir, Pakistan’s North-West Frontier Province (NWFP), and western and southern parts of the Kashmir valley in the Indian-held Kashmir. It also affected some parts of the Pakistani province of Punjab and the city of Karachi experienced a minor aftershock of magnitude 4.6. A total of 147 aftershocks were registered in the first day after the initial quake, of which one had a magnitude of 6.2 [1]. The death toll was 74,500 and 106,000 were injured. Most of the affected people lived in mountainous regions with access impeded by landslides that blocked the roads, leaving an estimated 3.3 million homeless in Pakistan. The UN reported that more than 4 million people were directly affected, prior to the commencement of winter snowfall in the Himalayan region. It is estimated that damage incurred is well over US 5 billion (30 billion Pakistani rupees). Hundreds of thousands of buildings collapsed or sustained severe damage. Apart from residential buildings most of the government offices, schools and hospitals were destroyed [2]. Relief efforts in many remote villages were hampered, as roads were buried in rubble and many affected areas remained inaccessible. Heavy equipment was needed to clear the roads and to rescue survivors buried under the earthquake wreakage, as many rescuers were picking the rubble with pickaxes and their bare hands, looking for survivors. Rescue efforts were also affected by the numerous aftershocks that continued to rattle the region and put rescue workers in danger as they search through the wreckage for survivors. In many areas there was no power, or adequate food or water, there was also danger of disease spreading, including measles. Distributing relief supplies to the victims was especially urgent as the victims face the risk of exposure to cold weather due to region’s high altitude and the approaching winter, food, medicine supplies, tents and blankets were identified by relief workers as essential items. Most of the roads were closed in the Northern sector near the earthquake, and some had been completely worked out or blocked by landslides, so the Pakistani army is fling supplies in the helicopters [3]. Inspite of suffering from the effects of earthquake both in life and property, Army Medical Corps (AMC) was mobilized immediately and provided commendable services both to military persons and civilian population of the affected areas. The dedication and professionalism of AMC was appreciated not only by the victims of the earthquake but also by the various disaster relief agencies. This issue of PAFMJ is dedicated to all the personnel of AMC who were involved in various relief efforts in any capacity. Although most of them provided useful services at the ground zero, yet they were supported by their fellow brothers at the base camps and tertiary care hospitals. This issue of PAFMJ will provide a collection of very useful experience of the medical support during devastated catastrophe.